Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1038/sj.jhh.1001391
|View full text |Cite
|
Sign up to set email alerts
|

The new oral angiotensin II antagonist olmesartan medoxomil: a concise overview

Abstract: The new orally active angiotensin II (A II) type-1 receptor antagonist olmesartan medoxomil is a prodrug, which is rapidly converted in vivo to the active metabolite, olmesartan. The pharmacology, antihypertensive efficacy and safety of olmesartan medoxomil and/or the pharmacologically active metabolite, olmesartan, have been evaluated in both non-clinical and clinical models. Orally administered olmesartan medoxomil is rapidly absorbed from the gastrointestinal tract and converted during absorption to olmesar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 7 publications
2
37
0
Order By: Relevance
“…The comparative studies demonstrated that, in patients with moderate-to-severe hypertension, olmesartan medoxomil (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) 1,7 Even at these lower doses, however, olmesartan maintained efficacy similar or superior to that of the comparators. In the studies comparing olmesartan with captopril and losartan, fewer patients were titrated to higher doses of olmesartan than in the case of either captopril or losartan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The comparative studies demonstrated that, in patients with moderate-to-severe hypertension, olmesartan medoxomil (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) 1,7 Even at these lower doses, however, olmesartan maintained efficacy similar or superior to that of the comparators. In the studies comparing olmesartan with captopril and losartan, fewer patients were titrated to higher doses of olmesartan than in the case of either captopril or losartan.…”
Section: Discussionmentioning
confidence: 99%
“…Olmesartan medoxomil is neither a substrate for, nor an inhibitor or inducer of, cytochrome P-450 isoforms. 7,8 This property, along with other general pharmacokinetic properties, limits the risk of pharmacokinetic interactions between olmesartan once daily (o.d.) and other co-administered drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that olmesartan is considered a very safe drug, [80][81][82][83] for which the US FDA has not dictated any unsafe dosing level. However, there are definite sequelae that some might consider to be 'adverse events'-autoimmune patients initiating this therapy appear to experience immunopathology, sometimes severe immunopathology.…”
Section: Our Therapeutic Approachmentioning
confidence: 99%
“…1a) is a prodrug and rapidly hydrolyzes in plasma during absorption to form its active metabolite olmesartan (Fig. 1b) (3)(4)(5). It is a selective AT1 subtype angiotensin II receptor blocker (6,7), which was recently approved by the US-FDA (8) to treat patients with hypertension.…”
mentioning
confidence: 99%